Procedure For Granting People's Business Credit In PT. Indonesian People's Bank Tamalate Unit Panakkukang Makassar Branch - Main Nining Hestiwi (Pustaka Digital Indonesia, 2021)
This study aims to describe how the procedure for granting People's Business Credit at PT. Bank Rakyat Indonesia Tamalate Unit Panakkukang Makassar Branch. The type of research used is descriptive qualitative. Data collection techniques used are observation, documentation and interviews. The interview process was carried out with Mantri and KUR customers. The data analysis method used is data reduction, data presentation, data examination and conclusion drawing. The results showed that the procedure for granting People's Business Credit at PT. Bank Rakyat Indonesia Tamalate unit Panakkukang Makassar Branch includes the credit application stage, credit investigation stage, credit decision stage and credit disbursement stage